Examination of game addiction studies conducted in Turkey: A systematic review study - Boz, Canahmet; Dinç, Mehmet (Frontiers in Psychiatry, 2023)
The aim of this study is to examine the methodological orientations in game addiction studies in Turkey between 2019-2022 in a holistic way and to present suggestions for new literature studies. For this purpose, only articles written in Turkish language were reviewed on Google Scholar. Open-access quantitative studies between 2019-2022 were included in our study. As a result, 69 out of 257 studies were found to comply with the predetermined criteria. The number of participants in these 69 studies, with a total sample size of 26,415, varies between 60 and 987. Almost half of the studies sample group is children (n=36). The majority of the studies examine the relationship between academic achievement, familial and social relationship problems, gaming behavior and game addiction in children and adolescents. It was found that gaming addiction was higher in male students compared to female students, especially between the ages of 14-15. Among children, male students play digital games more than girls, and they mostly prefer action-adventure, war, and racing games. Previous studies have concluded that the use of consoles and smartphones in adolescents and young adults has a high impact on digital game addiction. In the light of the findings, it is suggested that empirical studies on game addiction should be addressed with different aspects using new literature studies.